High fat diet consumption differentially affects adipose tissue inflammation and adipocyte size in obesity-prone and obesity-resistant rats - Poret, Jonquil M. (Int J Obes (Lond), 2017)
BACKGROUND/OBJECTIVES: Expanding visceral adiposity is associated with increased inflammation and increased risk for developing obesity-related comorbidities. The goal of this study was to examine high fat diet (HFD)-induced differences in adipocyte size and cytokine/chemokine expression in visceral and subcutaneous adipose depots in obesity-prone (OP) and obesity-resistant (OR) rats. METHODS: OP and OR rats were fed either a low fat diet (LFD, 10% kilocalories from fat) or HFD (60% kilocalories from fat) for 7 weeks. Adipocyte size and the presence of crown-like structures in epididymal and inguinal adipose tissue were determined. A multiplex cytokine/chemokine panel was used to assess the expression of inflammatory markers in epididymal and inguinal adipose tissues. RESULTS: A higher percentage of large adipocytes (> 5000 μm(2)) was detected in the epididymal and inguinal adipose tissues of OP rats and a higher percentage of small adipocytes (< 4000 μm(2)) was detected in the epididymal and inguinal adipose tissues of OR rats. More crown-like structures were identified in epididymal adipose tissue of OP rats fed a LFD, compared to OR rats. Consumption of a HFD increased the number of crown-like structures in OR, but not OP rats. Epididymal expression of pro-inflammatory cytokines (IL-1β, TNF-α) was higher in OP rats, compared to OR rats fed LFD. HFD consumption increased epididymal expression of GM-CSF, IL-1α, IL-1β, IL-6, MIP-2, and TNF-α in OP and OR rats. Inguinal expression of pro-inflammatory cytokines (IL-1α, IL-1β, TNF-α) was higher in OP rats, compared to OR rats. CONCLUSIONS: Overall, these data suggest that a higher susceptibility to developing obesity is characterized by large adipocytes and increased visceral adipose inflammation. Interestingly, in OR rats, the detrimental effects of HFD consumption on visceral adipose inflammation are evident with only small increases in weight and adiposity, suggesting that HFD also increases the risk for obesity-related comorbidities in OR rats.